Willingness of Long-Distance Train Passengers to Pay for Valuable Baggage Services - Priyanto, Sapto; Churniawan, Erifendi; Nopriyanto, Windi (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to analyze the willingness of long-distance train passengers to pay for a special valuable item storage service. Despite PT KAI recording an increase in passenger numbers in 2023, issues of lost belongings remain a significant concern, as experienced by passengers on the Tawang Jaya Premium and Kaligung trains. The study involved 276 respondents selected from long-distance train passengers. The Contingent Valuation Method (CVM) and binary logistic regression were used to understand the factors influencing the willingness to pay for this service. The findings indicate that 35% to 71% of passengers are willing to pay for the valuable item storage service. The price range considered reasonable by passengers is between Rp 5,000 and Rp 50,000. Several key factors influencing passengers’ willingness to pay include the reliability of the storage facilities provided, the security of the storage procedures, and the perceived risk of losing belongings on the train. These findings offer insights for PT KAI to consider providing this service, which could enhance passenger comfort and security while reducing the risk of lost items during travel.